2002
DOI: 10.1017/s0016672302009710
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular battlegrounds: conflict and cooperation between transposable elements

Abstract: Transposable elements (TEs) are genomic parasites that amplify their own representation on hosts' chromosomes by inserting into new positions. It is traditionally thought that their copy number is regulated by purifying selection that eliminates hosts with higher than average TE abundance. Here, we stress that selection due to beneficial or harmful interactions between TEs introduces a whole new dimension, with implications for TE evolutionary trajectories and TE loads on hosts. This framework poses new questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…While it is interesting to see these large changes, transposable elements violate the assumptions of the BD model in a number of ways and it can therefore be seen as a validation of our approach that they are identified as unlikely (see Discussion). Regardless of their lack of agreement with our model, the observation that one TE family has expanded and that one has contracted in S. cerevisiae suggests that there may be competition between these intracellular parasites (Leonardo and Nuzhdin 2002).…”
Section: Identification Of Unusually Evolving Gene Families In Sacchamentioning
confidence: 61%
“…While it is interesting to see these large changes, transposable elements violate the assumptions of the BD model in a number of ways and it can therefore be seen as a validation of our approach that they are identified as unlikely (see Discussion). Regardless of their lack of agreement with our model, the observation that one TE family has expanded and that one has contracted in S. cerevisiae suggests that there may be competition between these intracellular parasites (Leonardo and Nuzhdin 2002).…”
Section: Identification Of Unusually Evolving Gene Families In Sacchamentioning
confidence: 61%
“…It has been recently suggested that the relationships between genome components (including genes, transposable elements, or any sequence able to persist over evolutionary time) were similar to the relationships between individuals or species in ecosystems (10,49,50), although the possibility to apply ecological formalism to genome evolution remains questionable (51). Here, we brought substantial evidence that the relationships between autonomous and nonautonomous mariner TE copies were analogous to parasitism: Mos1 copies (the "hosts") are able to survive and replicate by themselves, whereas peach copies (the "parasites") are unable to transpose without Mos1 copies.…”
Section: Discussionmentioning
confidence: 99%
“…Canonical transposable elements, usually considered as parasitic sequences (Doolittle and Sapienza 1980;Orgel and Crick 1980) in the genome of an organism, play the role of the victim when they are in competition with mobile but nonautonomous elements. The complexity of TE evolution thus appears to be partly due to such a multilevel parasitism (Leonardo and Nuzhdin 2002).…”
Section: Discussionmentioning
confidence: 99%
“…What are the similarities between our TE dynamics models and existing predator-prey or host-parasite models? In other words, is this likeness relevant only to a vague, but convenient analogy, or is it an indication of a wide theoretical overlap between, on the one hand, the well-studied and still developing area of interspecific interactions, and, on the other hand, the embryonic theory of genomic ecology (Bascompte and Rodriguez-Trelles 1998;Leonardo and Nuzhdin 2002;Brookfield 2005)? There are indeed striking correspondences between our simple dynamics equations and the basic Lokta-Volterra prey-predator model (Lokta 1925;Volterra 1926).…”
Section: Discussionmentioning
confidence: 99%